PENGARUH PENGUMUMAN DIVIDEN TERHADAP HARGA SAHAM SEBELUM DAN SESUDAH EX-DIVIDEND DATE:Studi Terhadap Emiten Bursa Efek Indonesia Pada Tahun 2008 - Devi Sapmawati, - (2009)
This research is aimed tu analyze the influence of ex-dividend date on stock prices before and after the ex-dividend date at Indonesia Stock Exchange. Research sample is 80 emitens that share cash dividend in 2007 and 2008 consecutively. Emitens are grouped into three groups based on the value of the distributed dividend, the increased dividends were 52 emitens while the decreased dividends were 18 emitens, and the constant dividends were IO emitens. Research was conducted within the period of 30 days, 15 days before and 15 days after the ex-dividend date and analyzed using the event study method through two different test average pairs. Research result shows that stock prices before and after the ex-dividend date are statistically and significantly different. In the group of increased dividend, the stock prices of 37 emitens had significant differences between before and after the ex-dividend date while 15 emitens not. The decreased dividend experienced the same thing, the stock prices of 12 emitens had significant differences between before and after the ex-dividend date and the rest as many 6 emitens as didn't have significant differences. Io the group of constant dividend, the stock prices of six emitens came up with significant differences between before and after the ex-dividend · date; meanwhile three emitens didn't have significant differences between before and after the ex-dividend date. Those indicate that stock movement was obviously occurred as a market reaction of dividend announcement. Even so however, there are many things that investors need to consider in investing their fund, it is not only information that the company has issued, but also the company itself, including data and market conditions at that time.